2008
DOI: 10.1016/j.ijnurstu.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Back or neck-pain-related disability of nursing staff in hospitals, nursing homes and home care in seven countries—results from the European NEXT-Study

Abstract: Background: Musculoskeletal disorders are a widespread affliction in the nursing profession. Back or neck-pain-related disability of nursing staff is mainly attributed to physical and psychosocial risk factors. Objectives: To investigate which-and to what extent-physical and psychosocial risk factors are associated with neck/ back-pain-related disability in nursing, and to assess the role of the type of health care institution (hospitals, nursing homes and home care institutions) within different countries in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 28 publications
10
104
0
5
Order By: Relevance
“…Some studies have investigated the relationship of these stressors with health condition, 12,15 mental health, 4 coronary disease, 12,17 and symptoms, signs or disability arising from musculoskeletal problems. 9,10,22 In recent years special attention has been paid to nurses' health. These providers are usually subject to different physical loads determined by psychosocial stressors such as close attention, lack of understanding of the tasks, fast task performance, repetitive and fragmented tasks, low social support, lack of recognition and reward, high emotional demands, night work and lack of job security.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated the relationship of these stressors with health condition, 12,15 mental health, 4 coronary disease, 12,17 and symptoms, signs or disability arising from musculoskeletal problems. 9,10,22 In recent years special attention has been paid to nurses' health. These providers are usually subject to different physical loads determined by psychosocial stressors such as close attention, lack of understanding of the tasks, fast task performance, repetitive and fragmented tasks, low social support, lack of recognition and reward, high emotional demands, night work and lack of job security.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kim and colleagues found a modest increase in risk (OR=1.14; CI=1.08-1.19) for physical demands among PAS providers (Kim et al, 2010). Other studies of care providers have also found challenges in identifying the role of physical risk factors in WRMSDs or related disability (Ando et al, 2000;Simon et al, 2008), or determining the most problematic physical risk factor in home care (Cheung et al, 2006;Ono et al, 1995). Most of these studies, like ours, were self report surveys, and lacked validation from medical or disability records, which may lead to misclassification of cases or imprecision of the models.…”
Section: Temporal Factorsmentioning
confidence: 97%
“…The permanent physical environment issues included cramped conditions (strong evidence: Hale & Piggot, 2005;moderate evidence: Craven et al, 2012;Kalman & Andersson, 2014;Markkanen et al, 2007;Munck et al, 2011;Quinn et al, 2009;Skoglind-Ohman & Kjellberg, 2011;Swedberg et al, 2013), poor lighting (moderate evidence : Beer et al, 2014;Leiss, 2012;Munck et al, 2011), poor access to stairs (moderate evidence: Kim et al, 2010) and unsafe flooring (limited evidence: Conneeley, 1998). There are also less permanent risk factors associated with clutter and obstacles (moderate evidence : Beer et al, 2014;Leiss, 2012;Markkanen et al, 2007;Quinn et al, 2009;Skoglind-Ohman & Kjellberg, 2011) and awkward working positions for clinical, IT and writing tasks (strong evidence: Cheung et al, 2006;Dellve et al, 2003;Ono et al, 1995;Brulin et al, 2001; moderate evidence: Kim et al, 2010;Munck et al, 2011;Pohjonen et al, 1998;Quinn et al, 2009;Simon et al, 2008).…”
Section: Environments (Health Policy Community Physical and Social)mentioning
confidence: 99%
“…Evidence was found that identified physical risks associated with inadequate and missing equipment, e.g. lifting or bathing equipment which was the incorrect size and/or weight capacity for the patient (strong evidence: Hale & Piggot, 2005;moderate evidence: Craven et al, 2012;Faucett et al, 2013;Leiss, 2012;Pohjonen et al, 1998;Simon et al, 2008;Sims-Gould et al, 2013) and a lack of support for maintenance and training in medical devices (moderate evidence: Munck et al, 2011).…”
Section: Artefacts (Equipment and Technology)mentioning
confidence: 99%
See 1 more Smart Citation